Preclinical Evaluation of an Activity-Based Probe for Intraoperative Imaging of Esophageal Cancer. (14th July 2022) - Kennedy, Gregory T.; Azari, Feredun S.; Nadeem, Bilal; Chang, Ashley; Segil, Alix; Bernstein, Elizabeth; Desphande, Charuhas; Kucharczuk, John C.; Delikatny, Edward J.; Singhal, Sunil
Abstract : Background . Early detection and complete resection are important prognostic factors for esophageal cancer (EC). Intraoperative molecular imaging (IMI) using tumor-targeted tracers is effective in many cancer types. However, there are no EC-specific IMI tracers. We sought to test a cathepsin activity-based tracer (VGT-309) for EC resection. Methods . Murine (AKR, HNM007) and human (OE19) EC cell lines were screened for cathepsin expression by western blotting. In vitro binding affinity of VGT-309 was evaluated by fluorescence microscopy. Flank tumor models were developed by injecting EC cells into the flanks of BALB/c or athymic nude mice. Mice pretreated with a cathepsin inhibitor (JPM-OEt) were used to confirm on target binding. Animals were injected with 2 mg/kg VGT-309, underwent IMI, and were sacrificed 24 hours after injection. Results . Cathepsins B, L, S, and X were expressed by EC cell lines, and all cell lines were labeled in vitro with VGT-309. Fluorescent signal was eliminated when cells were pretreated with JPM-OEt. On biodistribution analysis, VGT-309 accumulated in the liver, kidneys, and spleen without other organ involvement. VGT-309 selectively accumulated in flank allografts and xenografts, with mean signal-to-background ratio of 5.21 (IQR: 4.18-6.73) for flank allografts and 4.34 (IQR: 3.75-5.02) for flank xenografts. Fluorescence microscopy and histopathological analysis confirmed the selective accumulation of the tracer in tumors compared to background normal tissues. Conclusions . VGT-309 is an effective tracer for IMI of esophageal cancer. There is potential for clinical translation both as an adjunct to endoscopic detection and for complete removal of disease during esophagectomy.